Development and evaluation of a generalized model of RAIM availability for single-, dual- and multi-satellite faults. (1st June 2022) - Ma, Xiaping; Yu, Kegen; He, Xiaoxing; Li, Qinzheng; Zhao, Lidu; Wang, Haicheng
Abstract: Receiver autonomous integrity monitoring (RAIM) fault monitoring and identification requires first to judge the geometric distribution of currently visible satellites based on performance indicators and to determine whether it is suitable for integrity monitoring, that is, to judge the availability of the RAIM algorithm. With the rapid development of the global navigation satellite system (GNSS), the possibility of dual-satellite faults and multiple-satellite faults in GNSS navigation and positioning has greatly increased. The existing literature mainly focuses on RAIM availability evaluation for single-satellite fault or dual-satellite faults, ignoring the occurrence possibility of multiple-satellite faults, and thus there is no unified RAIM availability evaluation model. To this end, we use the characters of the quadratic matrix to derive a generalized model of RAIM availability evaluation, and the model is suitable for situations of single-, dual- and multi-satellite faults. Based on the observation data of Beidou Navigation Satellite System (BDS) from 332 International GNSS Service (IGS) stations distributed globally on 24 March 2021 and the global ephemeris file, the global RAIM availability of BDS is evaluated. The results show that the generalized model of RAIM availability evaluation has a rigorous derivation process, strong applicability and easy implementation. When the cutoff elevation angle is greater than 5°, the average number of BDS visible satellites at 332 IGS stations worldwide is 12.289 and the average geometry dilution of precision value is 8.090. This can fully meet RAIM availability evaluation and integrity monitoring requirements at most IGS stations and regions. The RAIM availability of triple-satellite faults is lower than that of dual-satellite faults, and the RAIM availability of dual-satellite faults is lower than that of single-satellite fault. For the three different faults, the RAIM availability cannot fully satisfy the four stages in aviation all over the world. Among them, the RAIM availability is highest in the en-route (oceanic/continental low density) stage for all three types of faults, which is 93.146%, 74.848%, and 67.576%, respectively, while the non-precision approach stage has the lowest RAIM availability, which is 78.193%, 13.636%, 3.333% for the three types of faults, respectively.